In vitro stimulation of plasminogen activator release from vein walls by adrenaline. Issue 11 (November 1986) - Kjaeldgaard, A; Kjaeldgaard, M
Abstract : The effect of adrenaline on plasminogen activator release was studied in vitro in human vein biopsy specimens, in which the fibrinolytic activity was determined according to the fibrin slide technique. The tissue slides were covered with a thin fibrin film containing 10(-9) and 10(-7) M adrenaline and exposed for 30 to 60 minutes. In both concentrations highly significant (p less than 0.001) enhancement of fibrinolytic activity was shown, and the enhancement of fibrinolysis was most pronounced during the first 30 minutes of exposure. Stimulation of fibrinolysis was maximal after exposure to the physiological concentration of 10(-9) M, while no further increase was seen using the pharmacological concentration. These results show that adrenaline has a stimulant effect on tissue fibrinolysis in vitro, and this effect may account for the direct stimulation of fibrinolysis by adrenaline in vivo.